RETRACTED: Substantiation of the processing technology of wheat grains of early ripeness as the feed additive for fish - Pakhomov Viktor; Braginets Sergey; Bakhchevnikov Oleg; Sharaby Noureldin; Deev Konstantin (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001